Students\' perception of learning and educational environment in Behbahan Faculty of Medical Sciences - Neda Namnik; Leila Amir mohseni; sabaghan mohamad; Ali Veisi; Azimeh Ghorbanian (Health Science Monitor, 2022)
Background & Aims:  Learning is a complex process in which various factors are involved. The quality of the educational environment is one of the most important factors indicating the quality of education and students' learning. Thus, this study aimed to evaluate the learning environment for students of Behbahan Faculty of Medical sciences. Materials & Methods: This descriptive-analytical cross-sectional study was conducted at Behbahan Faculty of Medical Sciences with 115 students. Dundee Ready Education Environment Measure (DREEM) model was used for data collection that obtained 50 questions in five domains, including students' perceptions of learning, teachers' perceptions of teachers, students' academic self-perceptions, and students' perceptions of educational atmosphere and students' social self-perceptions. Data analysis was performed using descriptive statistics (frequency, percentage, mean and standard deviation) and one-way ANOVA. Results: The mean score of the overall DREEM score was 150.28 +13.03 out of a maximum of 200, showing favorable educational quality (75%). The lowest DREEM score was 64% in students' perceptions of learning, and the highest DREEM score was 79% in both students' perceptions of the professors and students' perceptions of the educational atmosphere. The mean difference for the DREEM subscale scores in different fields of study was statistically significant in all DREEM domains (p <0.05). Conclusion: Overall, the finding of this study showed that the educational environment of Behbahan Faculty of Medical Sciences was assessed as favorable by the majority of the students. But, considering the difference in results in different fields of study, the strengths and weaknesses of disciplines should be considered to improve the educational environments.